Manajemen Kurikulum Merdeka dalam Projek Penguatan Profil Pelajar Pancasila di SMP Negeri 3 Jombang - Fatimatuz Zahro; Nur 'Azah (Fakultas Agama Islam, Universitas Hasyim Asy'ari Tebuireng Jombang, 2024)
The independent curriculum is a flexible curriculum based on character and competency as well as creativity-based which is a set by the government strating in 2022/2023 at the primary and secondary eduation levels. In implementing the independent curriculum and P5 activities, there needs to be correct curriculum management. Based on the problems above, this research has 4 objectives. The research objectives are 1). To describe the independent curriculum management planning in the project to strengthen the profile of pancasila students SMP Negeri 3 Jombang. 2). To describe the implementation of independent curriculum management planning in the project to strengthen the profile of pancasila students SMP Negeri 3 Jombang. 3). To describe the evaluation of independent curriculum management in the project to strengthen the profile of pancasila students at SMP Negeri 3 Jombang. 4). To describe the supporting and inhibiting factors for independent curriculum management in the project to strengthen the profile of pancasila students at SMP Negeri 3 Jombang. The type of research is ase study research. The research was carried out using a descriptive qualitative approach. Data collection was carried out using interview, observation and documentation methods. Informants in this research consisted of the school principal, head of curriculum, team coordinator and team facilitator. Based on the research results, it was found that: P5 planning at SMP Negeri 3 Jombang started by forming a team of facilitators and coordinators, then determining a theme according to the theme of phase D, there was a special theme for SMP Negeri 3 Jombang, namely local wisdom and sustainable lifestyle. The implementation of P5 uses 3 themes, namely diversity, local wisdom and sustainable lifestyle. Furthermore, evaluation at SMP Negeri 3 Jombang is carried out once a month and uses two types of evaluation, namely process evaluation and results evaluation.